Impact of Growing Eucalyptus and Sal Monocultures on Soil in Natural Sal Area of Doon Valley - Jha, M. N.; Pande, P. (Indian Forester, 1984)
The present investigation deals with the impact of growing Eucalyptus and Sal monoeultures. On soil of Doon Valley by comparing it with the soil conditions under natural Sal forest. None of the monocultures could surpass the natural Sal as far as Organic matter accumulation, total N, P and available N, P, K are concerned. The Eucalyptus monoculture of fairly young age has shown higher accumulation of Organic matter in comparison to Sal monculture. The physical and chemical properties of the soil under Eucalyptus monoculture has been found to he better in comparison to sal monoculture. It has been concluded that raising Eucalyptus monocultore in natural Sal area causes no damage to the soil fertility and proves superior to long standing Sal monculture in Doon Valley.